2013
DOI: 10.1016/j.cognition.2013.01.009
|View full text |Cite
|
Sign up to set email alerts
|

When errors do not matter: Weakening belief in intentional control impairs cognitive reaction to errors

Abstract: The belief that one can exert intentional control over behavior is deeply rooted in virtually all human beings. It has been shown that weakening such belief - e.g. by exposure to 'anti-free will' messages - can lead people to display antisocial tendencies. We propose that this cursory and irresponsible behavior may be facilitated by a breakdown of neurocognitive mechanisms underlying behavioral adjustments. In the study reported here, we tested the hypothesis that weakening belief in intentional control reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
76
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 30 publications
5
76
2
Order By: Relevance
“…Participants showed post-error slowing when they failed to detect a nonthreatening face. To our knowledge, this is the first evidence of post-error adjustments in a visual-search task, where response latencies are much longer than what is typically found in studies using choice reaction time tasks (Laming, 1979;Rabbitt, 1966), Simon tasks (Rigoni, Wilquin, Brass, & Burle, 2013), or Stroop tasks (Suárez-Pellicioni, Núñez-Peña, & Colomé, 2013). This result supports the hypothesis that sequential control adjustments impact performance for a prolonged time period (Cheyne, Carriere, Solman, & Smilek, 2011).…”
Section: Discussionsupporting
confidence: 80%
“…Participants showed post-error slowing when they failed to detect a nonthreatening face. To our knowledge, this is the first evidence of post-error adjustments in a visual-search task, where response latencies are much longer than what is typically found in studies using choice reaction time tasks (Laming, 1979;Rabbitt, 1966), Simon tasks (Rigoni, Wilquin, Brass, & Burle, 2013), or Stroop tasks (Suárez-Pellicioni, Núñez-Peña, & Colomé, 2013). This result supports the hypothesis that sequential control adjustments impact performance for a prolonged time period (Cheyne, Carriere, Solman, & Smilek, 2011).…”
Section: Discussionsupporting
confidence: 80%
“…Previous literature has shown that the belief in free will is related to neural error detection Rigoni et al, 2013) and the ability to learn from one's own mistakes , and our findings demonstrate that these effects translate to better performance in related academic tasks.…”
Section: Discussionsupporting
confidence: 60%
“…Hence, trait self-control focuses on regulating the self and opposing urges and desires, whereas the belief in free will is about one's generalized belief in the freedom of action and the perceived capacity to choose one's own actions or to do otherwise (Baumeister, 2008). Studies have indeed shown that the belief in free will is associated with better self-control (Rigoni, Kühn, Gaudino, Sartori, & Brass, 2012;Rigoni et al, 2013). Linking the two constructs, we can conceptualize belief in free will as the perceived capacity of whether 12 or not and in what manner to exert self-control in different situations (Rigoni et al, 2012;Wertenbroch, Vosgerau, & Bruyneel, 2008), such that the belief in free will facilitates pointing the self in a desired direction, whereas trait self-control facilitates the long pursuit of this direction.…”
Section: Pretest: Belief In Free Will As a Unique Predictormentioning
confidence: 99%
See 1 more Smart Citation
“…According to Baumeister (2008), believing in free will increases one’s motivation and willingness to make efforts, therefore resulting in higher self-control. This argument has been supported by recent electroencephalography studies showing that inducing disbelief in free will changes the neural processes underlying voluntary action (Rigoni et al, 2011) and post error adaptation (Rigoni et al, 2013, 2015). Behavioral studies have likewise shown that the feeling of agency, that is, the pre-reflective feeling of being in control of one’s own actions (Synofzik et al, 2008) was reduced when participants were primed with disbelief in free will (Aarts and van den Bos, 2011; Lynn et al, 2014).…”
Section: Introductionmentioning
confidence: 84%